2022
DOI: 10.3390/biomedicines10102470
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Free Light Chains in Patients with Neuro-Sjögren

Abstract: Background: Sjögren’s syndrome (SS) is an autoimmune disease characterized by sicca symptoms and various extra-glandular manifestations. The diagnosis of SS requires sicca symptoms, anti-SSA(Ro)-antibody positivity, and/or pathological focus scores on a minor salivary gland biopsy. Previous studies have investigated different biomarkers in order to avoid invasive diagnostic procedures. It was found that kappa and lambda free light chains (KFLC and LFLC) in saliva are specific for SS. Methods: FLC concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…and colleagues examined serum and salivary FLC levels in patients with Sjögren's syndrome who had neurological symptoms (Neuro-Sjögren) and in neurological patients without the anti-SSA (Ro) antibodies (controls). The study found non-significant differences in FLC concentrations between the studied groups [74].…”
Section: Discussionmentioning
confidence: 58%
“…and colleagues examined serum and salivary FLC levels in patients with Sjögren's syndrome who had neurological symptoms (Neuro-Sjögren) and in neurological patients without the anti-SSA (Ro) antibodies (controls). The study found non-significant differences in FLC concentrations between the studied groups [74].…”
Section: Discussionmentioning
confidence: 58%
“…Both in RA and SS, concentrations of FLCs decreased after treatment [66]. FLC levels were also measured in saliva and serum of SS patients with neurological symptoms (Neuro-Sjögren) and neurological patients without the anti-SSA (Ro) antibodies (controls), but there were no differences in FLC concentrations between SS patients and control group [83].…”
Section: Rheumatic Diseasesmentioning
confidence: 98%
“…λFLCs in serum (pre-treatment) ↑ λFLCs in CSF (post-treatment) marker of systemic complications I monitoring response to therapy[82,83,86] …”
mentioning
confidence: 99%